A 31‐year trend of the hourly precipitation over South China and the underlying mechanisms. (25th January 2016) - Fu, Shenming; Li, Deshuai; Sun, Jianhua; Si, Dong; Ling, Jian; Tian, Fuyou
Abstract: On the basis of a newly developed intensive hourly observational precipitation dataset, the precipitation trend of South China was investigated. Results indicate that the hourly precipitation over South China featured a significant increasing trend, particularly for the extreme precipitation category. The trend is mainly due to the increasing frequency of the precipitation events. A possible mechanism accounting for this increasing trend was proposed: the global warming may be the original forcing for the trend, through its modulation on activities of the western Pacific subtropical high, but the low‐level vorticity is the most important direct trigger.